Epidemiological profile of tuberculosis in the prison population of Minas Gerais, Brazil - Teixeira Martins, Marcos Vinicius (2022)
Introduction: Tuberculosis is the major cause of health problems among communicable diseases and predominates as an etiology in cases of death from a single infectious agent. In the prison environment, this is even more evident, as overcrowding, poor nutrition, drug consumption and the coexistence of other diseases, associated with the precariousness of the health service, favors the spread of the disease within the walls and to the families of inmates. Currently, it is estimated that the incidence of tuberculosis in the population deprived of liberty corresponds to approximately 11.2% of new cases in the country, and this group represents only 0.3% of the Brazilian population.  Methods: In this context, the present study aims to carry out an epidemiological analysis of tuberculosis in the prison population of the state of Minas Gerais, Brazil, based on secondary data from the Notifiable Diseases Information System (SINAN), in addition to identifying the main factors related to this type of involvement using measures of dispersion, central tendency and frequency, as well as Student’s T tests for independent samples and Mann-Whitney U tests in cases where the assumptions for parametric tests were not met, considering a 95 % confidence interval. Results: 1880 cases of tuberculosis were registered, with a monthly average of 22.38 notifications. The proximity of the factors brown ethnicity, male sex, age between 20 and 29 years to the center of case density and between the use of alcohol, other drugs and the abandonment of treatment was notable. Conclusion: Thus, the need for new prevention strategies in this context is highlighted due to the high incidence of tuberculosis, often related to negligence and misinformation.